Haplotype Analysis of the First A4V-SOD1 Spanish Family: Two Separate Founders or a Single Common Founder? - Garcia, Cecilia; Vidal-Taboada, Jose Manuel; Syriani, Enrique; Salvado, Maria; Morales, Miguel; Gamez, Josep (Frontiers in Genetics, 2019)
Despite the genetic heterogeneity reported in familial ALS (fALS), Cu/Zn superoxide-dismutase (SOD1) gene mutations are the second most common cause of the disease, accounting for around 20% of all families (ALS1) and isolated sporadic cases (sALS). At least 186 different mutations in the SOD1 gene have been reported to date. The possibility of a single founder and separate founders have been investigated for D90A (p.91A) and A4V (p.A5V), the most common mutations worldwide. High-throughput SNP genotyping studies have suggested two founders for A4V (one for the Amerindian population and another for the European population) although the possibility that the two populations are descended from a single ancient founder cannot be ruled out. We used 15 genetic variants spanning the human chromosome 21 from the SOD1 gene to the SCAF4 gene, comparing them with the population reference panels, to demonstrate that the first A4V Spanish pedigree shared the genetic background reported in the European population.